Primary Extracranial Meningioma: The Royal Pearl Experience - Janakiram, Trichy Narayanan (Indian J Otolaryngol Head Neck Surg, 2015)
The extracranial occurrence of meningioma, which is a tumour of the central nervous system, is rare. Two cases of primary extracranial meningioma of the psammomatous variant are reported here. Both cases were managed successfully by endoscopic endonasal approach. Literature has been reviewed and their clinicopathological features are described.